We all fall down : living with addiction - Sheff, Nic. (New York : Little, Brown, 2011)
Sheff writes candidly about stints at in-patient rehab facilities, devastating relapses, and hard-won realizations about what it means to be a young person living with addiction.
Keywords: Sheff, Nic; Drug addicts -- California -- Biography -- Juvenile literature; Drug addicts -- Rehabilitation -- California -- Juvenile literature; Methamphetamine abuse -- California -- Biography -- Juvenile literature; Drug addicts -- California -- Biography; Drug addicts -- Rehabilitation -- California; Methamphetamine abuse -- California -- Biography